A revised embedded planning tool for intensive reading instruction - Wei, Yan; Lombardi, Allison; Simonsen, Brandi; Coyne, Michael; Faggella-Luby, Michael; Freeman, Jennifer; Kearns, Devin (Learning Disabilities: A Multidisciplinary Journal, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/057-076-036-438-880, pop00180 tex.type: [object Object]
Keywords: dept.rdg; dept.sed

Leveraging information technology literacy to enhance college and career readiness for secondary students with disabilities - Lombardi, Allison; Izzo, Margo V.; Gelbar, Nicholas; Murray, Alexa; Buck, Andrew; Johnson, Victor; Hsiao, Jay; Wei, Yan; Kowitt, Jennifer (Journal of Vocational Rehabilitation, 2017)
BACKGROUND: In the 21st century, information technology (IT) literacy is crucial for all students, and may better prepare students with disabilities for transition to postsecondary employment or education. OBJECTIVE: In this study, the potential of IT literacy embedded into an online transition curriculum is explored in the context of secondary special education. The curriculum aligns with Common Core State Standards in English Language Arts that are relevant to reading comprehension, writing, as well as searching for and analyzing sources of information online. METHODS: A quasi-experimental pretest-posttest design was utilized in six high schools. RESULTS: Findings show that intervention group students improved in IT literacy; whereas, comparison group students did not make similar gains. CONCLUSION: Implications for embedding transition services into specific courses and curricula for secondary students with Individualized Education Programs (IEPs) are discussed. © 2017-IOS Press and the authors. All rights reserved.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/066-237-439-502-729, pop00111 tex.type: [object Object]
Keywords: Article; Transition; adolescent; attention deficit disorder; autism; career; career readiness; college; comprehension; controlled study; curriculum; dept.rdg; dept.sed; disability; education program; emotional disorder; employment; female; high school student; human; information technology; intellectual impairment; language disability; learning disorder; literacy; major clinical study; male; quasi experimental study; special education; technology; vocational education; writing

Higher education and disability: A systematic review of assessment instruments designed for students, faculty, and staff - Lombardi, Allison; Gelbar, Nicholas; Dukes, III, Lyman L.; Kowitt, Jennifer; Wei, Yan; Madaus, Joseph; Lalor, Adam R.; Faggella-Luby, Michael (Journal of Diversity in Higher Education, 2018)
In this study, the literature in disability and higher education was examined, with a specific focus on assessment instruments. Published articles (n = 203) on development of new or refinement of existing instruments were reviewed for traits measured and psychometric rigor reported. Findings showed instruments are intended for professionals and students, and of the student instruments, broad categories are academic, nonacademic, and specific to a disability diagnosis. Not all instruments are limited to students with disabilities; many of the reviewed instruments can be utilized in higher-education settings on all students, faculty, and staff, regardless of disability. The implications of the findings undergird the urgency to prioritize disability as a facet of diversity within higher-education scholarship, and furthermore aid this prioritization by providing a catalogue of robust instruments to researchers and practitioners.
25 citations (Crossref) [2023-10-31] tex.eissn: 1938-8934 tex.unique-id: ISI:000426973700003
Keywords: Disability; assessment; campus climate; dept.rdg; dept.sed; peer-reviewed; program evaluation